STRATEGI PENGEMBANGAN USAHA KOPERASI UNIT DESA DI DESA ENGKERSIK KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Darmansah, Darmansah (Universitas Kapuas Sintang, 2025)
This study aims to analyze the development strategy of the Satrimas Village Unit Cooperative (KUD) in Engkersik Village, Sekadau Hilir District, Sekadau Regency. In determining its development strategy, cooperatives engaged in the savings and loan sector and other sectors such as trade must consider several important factors, including the amount of capital owned, cooperative products that have good market opportunities, and competitive product pricing. This research uses a qualitative approach with data collection methods through interviews, documentation studies, and observation. Aspects studied in the study include three main components, namely capital, products, and prices. The results showed that KUD Satrimas business capital sourced from member savings, residual income (SHU), and the results of capital investment from the oil palm plantation sector and other businesses. Products marketed include savings and loan services, transportation, and procurement, with marketing of palm oil FFB owned by plasma farmers who follow the market price of the buying company. Based on these findings, this study recommends that KUD Satrimas increase the variety of savings and loan products to provide more choices for members, which can indirectly increase the cooperative's capital. In addition, it is recommended to make investments by opening independent oil palm plantation land through cooperation between Satrimas KUD and local communities who have vacant land in the region.